How can the grasslands under rainfall events modify water balance in drought conditions - Minea Gabriel (Journal of Water and Land Development, 2018)
Taking into account the well-established influence of hillslopes grasslands on runoff processes, the purpose of this study was to investigate how grasslands can affect the water flow pathways on hillslopes, in drought conditions. This study was performed in experimental grassland at plot-scale (e.g., Festuca pratensis), in temperate humid continental climatic conditions of Curvature Subcarpathians, Romania. The rainfall, evapotranspiration, and soil moisture daily data, respectively 208 rainfall and 16 rainfall-runoff events data measured in grassland hills during the growing season (1 April up to 30 September 2015 and 2016) were used. Our results suggest that a runoff event response in extreme drought conditions occurs on grasslands only if precipitation exceeds the threshold of 31 mm Hortonian overland flow (HOF), while this threshold drops to 17 mm during moderate droughts and up to 8 mm for wet conditions. The rainfall events up to 16 mm proved to be insufficient to completely saturate the soil. Therefore, HOF has only a minor contribution in drought conditions, on grassland and light on bare soil. A complementary and negative effect of grasslands in drought conditions is the water resources suppressing on hillslopes.